Interactive effects of C-reactive protein levels on the association between APOE variants and triglyceride levels in a Taiwanese population. Issue 1 (December 2016) - Wu, Semon; Hsu, Lung-An; Teng, Ming-Sheng; Lin, Jeng-Feng; Chou, Hsin-Hua; Lee, Ming-Cheng; Wu, Yi-Ming; Su, Cheng-Wen; Ko, Yu-Lin
Abstract Background Apolipoprotein E (APOE) plays a major role in lipid metabolism and inflammation. However, the association betweenAPOE gene polymorphisms and serum triglyceride levels remains controversial. We tested the effects ofAPOE variants on triglyceride levels and their interactions with the inflammatory marker C-reactive protein (CRP) in a Taiwanese population. Methods Two APOE single nucleotide polymorphisms (SNPs) rs429358 and rs7412 were genotyped by TaqMan Assay using real time PCR in 595 healthy subjects attending the clinic for routine visits. Results After adjustment for clinical covariates, subjects carrying the rs429358-TT genotype and non-ε4 alleles were found to have higher CRP levels, whereas those with rs7412-CC genotype and non-ε2 alleles had significantly higher total and low-density lipoprotein cholesterol levels (allP  < 0.01). Using subgroup and interaction analyses, we observed significantly lower triglyceride levels in subjects carrying the rs429358-TT genotype and non-ε4 alleles in the low CRP group (P  = 2.71× 10−4 andP  = 4.32 × 10−4, respectively), but not in those in the high CRP group (interactionP =  0.013 and 0.045, respectively). In addition, multivariate stepwise linear regression analysis showed that subjects carrying the rs429358-TT genotype and non-ε4 alleles with low CRP levels had significantly lower triglyceride levels (P  < 0.001 andP  < 0.001, respectively). In addition, when combined with the risk alleles ofGCKR, APOA5 andLPL gene variants, we observed that triglyceride levels increased significantly with the number of risk alleles (P  = 2.9 × 10−12 ). Conclusions The combination of SNPs and ε alleles at theAPOE locus is involved in managing lipid and CRP levels in the Taiwanese population.APOE polymorphisms interact with CRP to regulate triglyceride levels, thus triglyceride concentration is influenced by both the genetic background of theAPOE locus and the inflammatory status of a subject.